Memoirs of the Protestant Episcopal Church in the United States of America,from its organization up to the present day ... - White, William (Benson collection of hymnals and hymnology, 1836)
I. A narrative of the organization and of the early measures of the Church. -- II. Additional statements and remarks. -- III. An appendix of original papers.